An electrical equivalent circuit to simulate the output power of an AlGaAs/GaAs planar Gunn diode - Maricar, Mohamed Ismaeel; Khalid, Ata; Dunn, Geoff; Greedy, Steve; Thomas, David W.P.; Cumming, D.R.S.; Oxley, C.H. (Wiley, 2018)
The planar Gunn diode offers the potential of microwave, milli-metric and THz based oscillator which can be fabricated as part of a microwave monolithic integrated circuit (mmic). To-date the RF output power has been too low for many applications. This paper looks at a simple electrical equivalent circuit model representation of an aluminium gallium arsenide (AlGaAs) based planar Gunn diode with an active channel length of approximately 4μm and width of 120μm. The model indicated a maximum RF output power of +5dBm compared with published experimental results of –19dBm for similar diodes.